Bovine lactoferrin free of lipopolysaccharide can induce a proinflammatory response of macrophages - Zemankova, Nada; Chlebova, Katarina; Matiasovic, Jan; Prodelalova, Jana; Gebauer, Jan; Faldyna, Martin (BMC veterinary research, 2016)
BACKGROUND: Lactoferrin (LF) is an 80 kDa glycoprotein which is known for its effects against bacteria, viruses and other pathogens. It also has a high potential in nutrition therapy and welfare of people and a variety of animals, including piglets. The ability to bind lipopolysaccharide (LPS) is one of the described anti-inflammatory mechanisms of LF. Previous studies suggested that cells can be stimulated even by LPS-free LF. Therefore, the aim of our study was to bring additional information about this possibility. Porcine monocyte derived macrophages (MDMF) and human embryonic kidney (HEK) cells were stimulated with unpurified LF in complex with LPS and with purified LF without bound LPS. RESULTS: Both cell types were stimulated with unpurified as well as purified LF. On the other hand, neither HEK0 cells not expressing any TLR nor HEK4a cells transfected with TLR4 produced any pro-inflammatory cytokine transcripts after stimulation with purified LF. This suggests that purified LF without LPS stimulates cells via another receptor than TLR4. An alternative, TLR4-independent, pathway was further confirmed by analyses of the NF-kappa-B-inducing kinase (NIK) activation. Western blot analyses showed NIK which activates different NFκB subunits compared to LF-LPS signaling via TLR4. Though, this confirmed an alternative pathway which is used by the purified LF free of LPS. This stimulation of MDMF led to low, but significant amounts of pro-inflammatory cytokines, which can be considered as a positive stimulation of the immune system. CONCLUSION: Our results suggest that LF's ability is not only to bind LPS, but LF itself may be a stimulant of pro-inflammatory pathways.
Keywords: LPS; signální transdukce; Inflammation; Protein Binding; HEK293 Cells; Toll-Like Receptor 4; cytokiny; Gene Expression Regulation; Lipopolysaccharides; zánět; Lactoferrin; protein-serin-threoninkinasy; Signal Transduction; Cytokines; Intracellular Signaling Peptides and Proteins; TLR4; regulace genové exprese; toll-like receptor 4; Macrophages; Protein Serine-Threonine Kinases; Swine; intracelulární signální peptidy a proteiny; NFκB; zvířata; HEK293 buňky; Humans; Inflammatory cytokines; lipopolysacharidy; vazba proteinů; NIK; makrofágy; prasata; laktoferrin; lidé; Animals